The work of Vojin Komadina in the repertoire of the Zagreb Music Biennale - Marinković Miloš; Đukić-Čamur Snježana (Zbornik Radova Akademije Umetnosti)
In 1961, the first Zagreb Music Biennale (MBZ) was held in Yugoslavia, an international festival of contemporary music with two main objectives: to familiarize the domestic audience with contemporary musical endeavors worldwide and to contribute to the international recognition of Yugoslav endeavours. Vojin Komadina (1933-1997) made his debut at the fourth MBZ in 1967 and until the 1980s remained the only composer from Bosnia and Herzegovina whose works were performed at this most significant contemporary music festival in Yugoslavia. Drawing on insights into stylistic and compositional tendencies in Yugoslav music during the 1960s, 1970s, and 1980s, this paper examines the various contexts of performances of Komadina's works at the Zagreb Music Biennale. The author's works are analyzed in relation to the MBZ's selection criteria, establishing Vojin Komadina's position at this international festival. Another important aspect of the study is the reception of Komadina's work from the MBZ repertoire. By considering critical reviews of this event published in the press during the second half of the 20th century, including musical periodicals (Zvuk, Promusica), cultural and social magazines (Telegram, 15 dana), and daily newspapers (Vjesnik, Večernji list, Oslobođenje), this research reveals various (even completely opposite) reactions of contemporary music critics to Komadina's works from the biennial repertoire. Although Vojin Komadina's works have not been performed at the MBZ since 1983, this does not diminish the significance of this festival as a place of international recognition for musicians in the professional career of the Bosnian-Herzegovinian composer. The fact that from the second half of the 1960s to the first half of the 1980s, Komadina was the only author from Bosnia and Herzegovina to participate in the Zagreb Music Biennale, the largest contemporary music festival in this part of Europe, speaks to the composer's status not only within domestic, Bosnian-Herzegovinian, and Yugoslav contexts but also in international frameworks.